2015
DOI: 10.1038/nature16039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagnostics for the detection of asymptomatic Plasmodium falciparum infections to inform control and elimination strategies

Abstract: The global burden of malaria has been substantially reduced over the past two decades. Future efforts to reduce malaria further will require moving beyond the treatment of clinical infections to targeting malaria transmission more broadly in the community. As such, the accurate identification of asymptomatic human infections, which can sustain a large proportion of transmission, is becoming a vital component of control and elimination programmes. We determined the relationship across common diagnostics used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
215
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(233 citation statements)
references
References 63 publications
16
215
1
1
Order By: Relevance
“…Specifically, submicroscopic malaria has been associated with older age, presumably due to partial immunity. 6,15,16 Although high levels of bed net usage during the study period suggested that bed nets may be partly responsible for this finding, bed net usage was not a risk factor for subpatent infection in our models, a finding consistent with prior reports. 16 Submicroscopic infections are also thought to be more common in settings of low transmission intensity.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Specifically, submicroscopic malaria has been associated with older age, presumably due to partial immunity. 6,15,16 Although high levels of bed net usage during the study period suggested that bed nets may be partly responsible for this finding, bed net usage was not a risk factor for subpatent infection in our models, a finding consistent with prior reports. 16 Submicroscopic infections are also thought to be more common in settings of low transmission intensity.…”
supporting
confidence: 82%
“…1 Even if most subpatent infections in these young children are asymptomatic, they may represent a transmission reservoir that requires further study and may need to be addressed by ongoing malaria control efforts. 6 Age less than 5 years was a risk factor for subpatent malaria in our cohort, a finding that differs from other published reports. Specifically, submicroscopic malaria has been associated with older age, presumably due to partial immunity.…”
contrasting
confidence: 57%
See 2 more Smart Citations
“…In a systematic review, Okell et al [18] also found that older age groups were generally associated with increased sub-microscopic carriages. Our results are in tandem agreement with previous studies showing that molecular detection techniques have greater sensitivity and specificity than either microscopy for the identification of single and mixed species infections [23,[39][40][41][42], as well as sub-microscopic infections [11,43]. The detection of Plasmodium parasites at very low density parasitaemia is difficult by microscopy and thus requires a molecular approach especially for surveillance or epidemiological studies [44].…”
Section: Discussionsupporting
confidence: 82%